Everyday Telepresence: Emerging Practices and Future Research Directions - Rae, Irene; Mutlu, Bilge; Olson, Gary M.; Olson, Judith S.; Takayama, Leila; Venolia, Gina (CHI 2015 Extended Abstracts, 2015)
As network availability becomes ubiquitous, users are leveraging this access to establish their presence in remote locations through the use of commercially available telepresence technologies. With the increasing adoption of systems, new questions are emerging about how these technologies affect user interactions and relationships. Our goal for this workshop is to bring an interdisciplinary group of telepresence researchers together to trade perspectives, fostering new opportunities for collaboration and to facilitate discussion on how to advance the field.